2019
DOI: 10.1016/j.cmi.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Human polyspecific immunoglobulin attenuates group A streptococcal virulence factor activity and reduces disease severity in a murine necrotizing fasciitis model

Abstract: The clear reduction in disease severity in IVIG-treated mice and inhibition of virulence factor activity in mouse and human sera suggest that IVIG may be beneficial in invasive group A Streptococcus infections such as NF in addition to streptococcal toxic shock syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…This is in line with the recent metaanalysis of IVIG-therapy in clindamycin-treated Streptococcal Toxic Shock Syndrome (STSS) in which adjunctive IVIG was associated with a survival benefit [2]. Mechanistic actions of IVIG in this setting include neutralization of GAS superantigens and dampening of inflammation [3][4][5][6][7].…”
Section: Introductionsupporting
confidence: 68%
“…This is in line with the recent metaanalysis of IVIG-therapy in clindamycin-treated Streptococcal Toxic Shock Syndrome (STSS) in which adjunctive IVIG was associated with a survival benefit [2]. Mechanistic actions of IVIG in this setting include neutralization of GAS superantigens and dampening of inflammation [3][4][5][6][7].…”
Section: Introductionsupporting
confidence: 68%
“…Since this effect is the result of the extracellular binding between HSA and SLO, from a clinical point of view the demonstration of a neutralizing effect itself rather than the protective effect on different types of adopted cellular models is the most relevant result. In vivo studies clearly demonstrated that the inhibition of SLO activity was significantly associated with a disease severity reduction in necrotizing fasciitis, necrotizing myositis, bacteremia, and soft tissue infection models ( 54 , 55 ). Therefore, we hypothesize that HSA levels could affect streptococcal diseases severity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the actions of IVIG have been demonstrated in vitro and in mice experimental models, including neutralization of circulating superantigens and reduction of the systemic inflammatory response ( 22 , 23 ). A recent study analyzed the effects of IVIG on virulence factor activity in three different ways: in vitro, in vivo in a murine infection model, and ex vivo in patients ( 24 ). In vitro , SLO and Sda1 activities were reduced.…”
Section: Methodsmentioning
confidence: 99%
“…In the murine infection model, mice treated with IVIG had smaller skin lesions and a lower SLO activity. Moreover, serum from patients with iGAS had a reduced SLO and Sda activity after IVIG was administrated compared with before such treatment ( 24 ). In addition, plasma of STSS-patients treated with IVIG was able to neutralize streptococcal superantigens and completely inhibit cytokine production ( 25 ), suggesting a clinical interest of such adjunctive therapy for these patients.…”
Section: Methodsmentioning
confidence: 99%